Amiri's First Praise Ghazali Analysis - Zebokhon Qobulova; Dilzodakhan Abdullayeva (Genius Journals, 2023)
This article analyzes Amiri's first praise ghazal. The philosophical content is proved by religious literature. The artistic skills of the poet are revealed.
Keywords: Amiri; Qur'an; praise; ghazal